The influence of liquidity, profitability, and solvency on stock price - Adriansyah, Fachri; Sherlita, Erly (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to investigate and analyze how financial ratios affected the stock prices of food and beverage firms. The current ratio (CR), return on assets (ROA), and debt-to-equity ratio are examples of financial ratios (DER). The research methodology used in this study is explanatory. The sample size for this study was 20 food and beverage firms listed on the Indonesia Stock Exchange for the years 2018 to 2021 using a non-probability sampling method with a purposive selection strategy. The annual reports of the food and beverage companies listed on the Indonesia Stock Exchange were the source of secondary data for this study. Multiple linear regression analysis, which is computed using the SPSS 23 program, is the analytical technique used. The results of this study indicate that the Current Ratio (CR) partially has no effect on stock prices, Return on Assets (ROA) partially has a significant effect on stock prices, Debt to Equity Ratio (DER) has no effect on stock prices and the Current Ratio (CR), Return on Assets (ROA) and Debt to Equity Ratio (DER) simultaneously have a significant effect on stock prices.